Numerical Simulation Platform for a Generic Aircraft Flight Dynamic Simulation - Adila Arif, Adam; ., Stepen; Adhy Sasongko, Rianto (International Journal of Engineering and Technology, 2018)
Flight simulation has been used for many purposes in several decades, started from pilot training, engineering purposes, even just for a hobby. In its development, computing technology has a vital role in aircraft simulation. Nowadays, people do an aircraft simulation mostly by using a set of the computing device and complementary equipment such as a joystick. On the other hand, engineers use aircraft simulation in order to evaluate the aircraft in many aspects such as flight performance, handling quality, and controllability. This paper proposes a simulation system to do an engineering simulation especially to evaluate controllability of an aircraft utilizing X-Plane 10, Python and MATLAB. This system can manipulate aircraft loading configuration and failure on aircraft systems, set the environment condition, and observe control-related flight parameters in MATLAB whilst the aircraft is still flying in the X-Plane 10 at the same time. The system had been tested and proved could work well with X-Plane 10.Â Â